MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS MELALUI MODEL PEMBELAJARAN EXPERIENTIAL LEARNING BERBASIS ZONE OF PROXIMAL DEVELOPMENT (ZPD) - Roby Firdian Ruswanda; Achi Rinaldi; Siska Andriani; Gusti Ayu Farah Nabilla (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2020)
This research's background is the students' mathematical creative thinking abilities that are rarely of concern so that they are generally classified as low. This study aims to determine the Zone of Proximal Development Experiential Learning model's effect based on improving mathematical creative thinking skills. The design of this study uses the Quasi-Experimental Design form. This study's population were students of class VII SMP Negeri 19 Bandar Lampung with a sample of two experimental classes and one control class. Data analysis used the One Way Anova test, and the significance level was 5%. Based on the average increase, the Experiential Learning Model, based on the Zone of Proximal Development, is as good as the Experiential Learning Model. The Experimental Learning Model is based on Zone Of Proximal Development is better with conventional learning, Experiential Learning Model is better with conventional learning. Latar belakang penelitian ini adalah kemampuan berpikir kreatif matematis peserta didik yang jarang menjadi perhatian sehingga secara umum masih tergolong rendah. Tujuan dari penelitian ini mengetahui pengaruh model pembelajaran Experiential Learning berbasis Zone Of Proximal Development untuk meningkatkan kemampuan berpikir kreatif matematis. Desain penelitian ini menggunakan bentuk Quasi Experimental Disign. Populasi pada penelitian ini yaitu siswa kelas VII SMP Negeri 19 Bandar Lampung dengan sampel dua kelas eksperimen dan satu kelas kontrol. Analisis data menggunakan uji One Way Anova dan taraf signifikan 5%. Berdasarkan rata – rata peningkatan disimpulkan bahwa Model pembelajaran Experiential Learning berbasis Zone Of Proximal Development sama baiknya dengan Model pembelajaran Experiential Learning, Model pembelajaran Experiential Learning berbasis Zone Of Proximal Development lebih baik dengan pembelajaran konvensional, Model pembelajaran Experiential Learning lebih baik dengan pembelajaran konvensional.